Practice in Nursery Weed Control—Review and Meta-Analysis - Yu, Ping; Marble, Stephen Christopher (Frontiers in Plant Science, 2022)
Weeds, as one of the biggest challenges in the nursery industry, have been controlled by various methods, such as chemical and non-chemical practices. Although these practices have been widely established and tested to control weeds, there is no systematic or meta-analysis review to provide quantitative weed control efficacy information of these practices. To provide a systematic understanding of weed control practices in nursery production, a visualization research trend, a systematic review, and a meta-analysis were conducted. A total of 267 relevant studies were included for the research trend and 83 were included in the meta-analysis. The results in this study showed that interests in nursery weed control have switched dramatically in the past 2–3 decades (1995–2021) from chemical dominant weed control to chemical coexistent with non-chemical techniques. Developing new management tactics and implementing diverse combinations of integrated weed management present the future trend for weed control. The systematic review results showed that chemical methods had the highest weed control efficacy, while non-chemical had the lowest on average, nonetheless, all three weed control practices (chemical, non-chemical, and combined) reduced the weed biomass and density significantly compared with when no strategy was employed. Weed control challenges could be the catalyst for the development of new non-chemical and integrated weed control techniques.